A case study about Covid-19’s effects on liner shipping - The impact of the Covid-19 pandemic on outbound and inbound flows between Sweden and China - Olsson, Sten; Yang, Richard (My University, 2021)
No one expected the virus Covid-19 to affect the whole world. Most countries initiated lockdowns, quarantine and restrictions. E.g., China shut down their exports. However, Sweden adapted another strategy, instead of proceeding to lockdowns they relied on social distancing. Furthermore, the strategy benefited the Swedish economy and shipping lines operating in Sweden. Delimitations as routes, vessels, industry, type of study, time span and unit carrier were included. A literature study was conducted to form a theoretical basis for the thesis’ research questions. Additionally, a qualitative case study was conducted. The case study is based on semi-structured interviews and internal documents. This thesis attempts to examine three research questions, all based on the novel Covid-19 virus. ● How was the Covid-19 impact compared to other historical crises in terms of inbound and outbound flows? ● How has the Covid-19 pandemic affected the inbound and outbound flows of containers for shipping lines between China and Sweden, comparing the first and second half of 2020? ● How has the pandemic and its side effects affected the relationship between shipping lines and their customers? Regarding the first research question, the thesis came to the conclusion that there was not much similarity from historical events alike Covid-19. SARS occurred 2003 and only spread in East Asia. The differences in virus structure and geographical spread, as well as the lack of published or documented studies made conclusions of similar pandemics uninterpretable. Compared to the financial crisis, Covid-19 had few similarities. E.g., economic decline. However, the financial crisis took years for the global economy to recover from. Whereas, Covid-19 only took months. Regarding the second research question, it was obvious from the case study that the Swedish import was declining in the first half but recovered and surged in the second half. The Swedish export was steady the whole year. Finally, the case study found that the sudden increase in demand for transport exceeded the available containers. which bottlenecked shipping lines and the cargo owners’ supply chains. Despite this, the cargo owners and other customers of shipping lines were overall understanding of the disruptions caused by the pandemic.
Keywords: Covid-19; Corona; Shipping; Liner shipping; Case study; Shipping 2020; Container; Export; Import; Sweden